Respiratory Polygraphy Patterns and Risk of Recurrent Cardiovascular Events in Patients With Acute Coronary Syndrome - Zapater, Andrea; Solelhac, Geoffroy; Sánchez-de-la-Torre, Alicia; Gracia-Lavedan, Esther; Benitez, Ivan David; Torres, Gerard; De Batlle, Jordi; Haba-Rubio, José; Berger, Mathieu; Abad, Jorge; Duran-Cantolla, Joaquín; Urrutia, Amaia; et al. (Frontiers in Medicine, 2022)
Introduction: Obstructive sleep apnea (OSA) severity is based on the apnea-hypopnea index (AHI). The AHI is a simplistic measure that is inadequate for capturing disease severity and its consequences in cardiovascular diseases (CVDs). Deleterious effects of OSA have been suggested to influence the prognosis of specific endotypes of patients with acute coronary syndrome (ACS). We aim to identify respiratory polygraphy (RP) patterns that contribute to identifying the risk of recurrent cardiovascular events in patients with ACS. Methods: Post-hoc analysis of the ISAACC study, including 723 patients admitted for a first ACS (NCT01335087) in which RP was performed. To identify specific RP patterns, a principal component analysis (PCA) was performed using six RP parameters: AHI, oxygen desaturation index, mean and minimum oxygen saturation (SaO2), average duration of events and percentage of time with SaO2<90%. An independent HypnoLaus population-based cohort was used to validate the RP components. Results: From the ISAACC study, PCA showed that two RP components accounted for 70% of the variance in the RP data. These components were validated in the HypnoLaus cohort, with two similar RP components that explained 71.3% of the variance in the RP data. The first component (component 1) was mainly characterized by low mean SaO2 and obstructive respiratory events with severe desaturation, and the second component (component 2) was characterized by high mean SaO2 and long-duration obstructive respiratory events without severe desaturation. In the ISAACC cohort, component 2 was associated with an increased risk of recurrent cardiovascular events with an adjusted hazard ratio (95% CI) of 2.44 (1.07 to 5.56; p-value=0.03). For component 1, no significant association was found for the risk of recurrent cardiovascular events. Conclusion: A RP component, mainly characterized by intermittent hypoxemia, is associated with a high risk of recurrent cardiovascular events in patients without previous CVD who have suffered a first ACS.